Evaluating teacher multilingualism across contexts and multiple languages: validation and insights. Issue 8 (August 2020) - Calafato, Raees
Abstract: In response to the need for quantitative instruments that can provide insights into language teacher multilingualism on a large scale, this article discusses the development of the MULTITEACH questionnaire via a five-stage process that consisted of a critical review of research on teacher multilingualism, seminar and practitioner consultations, a pilot study, reliability tests, and principle component analysis (PCA), followed by a larger study involving 460 multilingual language teachers and factor analysis to confirm the PCA. The questionnaire thus validated provides a comprehensive quantitative measure of assessing language teacher multilingualism across multiple foreign languages and in diverse contexts. A discussion of the factors influencing teacher multilingualism has also been included based on the findings from the larger study of 460 multilingual teachers. Abstract : Education; Multilingualism; Teacher education; Teacher practices; Evaluation; Teacher beliefs; Language teaching; Second language acquisition